A fatigue-resistant steel plate in marine environment and its production method
By adding specific chemical components and nanophase to the steel plate to form a composite corrosion-resistant structure, the fatigue-corrosion coupling problem of marine structures under strong storms and large wave load conditions in the South China Sea waters is solved, which significantly improves the corrosion resistance and fatigue resistance of the steel plate, and ensures the safety and durability of the marine structure.
Patent Information
- Application Number
- CN202211611544.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-12-14
AI Technical Summary
High temperature, high salt and strong storm environments in the South China Sea have caused marine structures to face serious durability and safety challenges under the fatigue-corrosion coupling problem, and the existing technology is difficult to effectively solve this problem.
A specific steel chemical composition is used, containing elements such as C, Si, Mn, V, N, Cu, Ni, Mo, Re, Cr, REM, Sn, Ti, P and S. Through the addition and synergistic action of composite trace elements, a corrosion-resistant structure of 55-70% bainite + 23-35% ferrite is formed. Through specific smelting and preparation processes, 15-25nm V(C, N) and Mo2C nanophase, and 17-25nm Cu nanophase, to improve the corrosion resistance and fatigue resistance of the steel plate.
The corrosion resistance and fatigue resistance of the steel plate are significantly improved. The corrosion resistance is 14-16% higher than that of 3Ni system steel, and has good mechanical properties, structural safety and welding properties. It can effectively extend the service life of marine structures in strong storm marine environments such as the South China Sea.
Smart Images

Figure BDA0003999611150000081 
Figure BDA0003999611150000091 
Figure BDA0003999611150000092
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal material preparation, and particularly relates to an anti-fatigue steel plate in a marine environment and a production method thereof. Background Art
[0002] The South China Sea covers an area of 3.56 million square kilometers and is the main waterway for east-west exchanges. At present, nearly 90% of my country's energy imports have to pass through the South China Sea. In terms of ensuring global energy transportation and military strategic significance, the South China Sea has great geostrategic value and is of great significance to national security. In addition, the South China Sea has extremely rich natural resources and strategic value. It is one of the richest seas, with more than 30 billion tons of oil resources, more than 68 billion tons of oil and gas equivalent of methane hydrate resources, and the largest wind and wave energy resources.
[0003] The South China Sea has unique characteristics of high temperature (ocean surface temperature 25-28℃, up to 30℃), high salinity (Cl - Deposition rate 1.12mg / 100cm 2 d or above), strong storms (maximum wave height of nearly 30m), and other strong corrosive and fatigue damage environmental factors. The natural environment is harsh and the material corrosion problem is very prominent. According to the ISO9223 classification standard, the corrosion level of materials in this area can reach the highest level C5. Compared with other regions, surface ships, offshore floating platforms, island and reef buildings, equipment and facilities currently in service in this environment will suffer from severe corrosion prematurely even if corrosion protection measures are taken. According to statistics, the failure rate of equipment and facilities in service in the South China Sea is three times that of other sea areas and about 10 times that of the mainland. It causes nearly 1 trillion yuan of economic losses to the country every year. The South China Sea environment includes island and reef construction, resource mining platforms, offshore life auxiliary equipment, offshore clean energy development equipment, etc., mainly steel structures. With the gradual implementation of the national marine and South China Sea strategy, the amount of steel used will reach 1 million tons / year in the next 5-10 years.
[0004] In addition to facing the harsh and complex marine environment of high salt and high temperature during service, the marine engineering structures in the South China Sea are often subjected to environmental loads such as sea breeze, waves and currents, as well as repeated effects of dynamic loads of operations. For example, an offshore platform with a design life of 20-25 years may experience hundreds of millions of cycles of alternating stress caused by wave action during its service life. In addition, marine environment construction engineering structures, especially offshore platforms, often have to support various equipment with a total mass of hundreds of tons, which causes them to be subjected to extremely high working stress. In addition, due to their large size and thickness, joint defects such as microcracks, pores, slag inclusions, and unfused joints can easily become sources of cracks for corrosion and fatigue, resulting in reduced fatigue toughness. Therefore, fatigue issues must also be considered during the use of marine engineering structures and their service. At present, the research and development of special materials for the harsh environment of the South my country Sea is not systematic, and the main research is on the corrosion resistance of materials. The domestic patent application number 201710075154.0 "A high corrosion-resistant low-alloy steel suitable for high-temperature coastal environment" has better corrosion resistance than Q235 carbon steel and other weathering steels. Due to the use of a high Ni system and alloying with elements such as Cu and Mo, the problem is that the cost is relatively high, and due to the high alloying and carbon equivalent, there are problems with welding performance; At present, there is no report on fatigue-resistant steel for materials under the conditions of strong corrosion, strong storms, and large wave loads in the South China Sea. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide an anti-fatigue steel plate and a production method thereof in a marine environment, so as to solve the fatigue-corrosion coupling problem faced by marine structures under strong storm and large wave load conditions.
[0006] To solve the above problems, the technical solution adopted by the present invention is as follows: an anti-fatigue steel plate for marine environment, the chemical composition of the steel grade comprises, by weight percentage, C: 0.02-0.04wt%, Si: 0.15-0.3wt%, Mn: 0.4-0.6wt%, V: 0.04-0.06wt%, N: 0.008-0.012wt%, Cu: 0.2-0.4wt%, Ni: 1-2wt%, Mo: 0.1-0.2wt%, Re: 0.021-0.034wt%, Cr: 1.5-2wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.015-0.02wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
[0007] Furthermore, the steel plate contains 55-70% bainite + 23-35% ferrite (including 6-12% acicular ferrite) structure, the percentage is area percentage; contains V (C, N) and Mo dispersedly precipitated with an average size of 15-25nm 2C nanophases, the average spacing between these phases is 1.2-2.5μm, and they contain Cu nanophases with an average size of 17-25nm, and the average spacing between the phases is 1-2μm.
[0008] Furthermore, the dispersed V (C, N) and Mo 2 The size of the C nanophase is 10-30 nm, and the size of the Cu nanophase is 15-30 nm.
[0009] Furthermore, the average grain size of the surface layer -1 / 8 thickness of the steel plate is 15-25 μm.
[0010] Furthermore, the yield strength of the steel is 420-460 MPa, the yield strength ratio is ≤0.75, the impact energy at -40°C is not less than 180 J, the elongation is ≥20%, and the cross-sectional shrinkage is ≥68%.
[0011] Furthermore, when the loading stress ratio is 0.1, the frequency is 90HZ, and the maximum stress is 0.7Rel, the number of cycles reaches 10 7 The sample does not break, -20℃CTODδm>0.62mm.
[0012] Furthermore, a cyclic immersion test was conducted in a simulated South China Sea seawater splash zone, and the corrosion resistance was 84-86% relative to that of 3Ni system steel.
[0013] The present invention provides a method for producing fatigue-resistant steel plates in marine environments, including smelting, continuous casting, billet heating, rolling and offline processing, the specific contents of which are as follows:
[0014] Billet heating: The temperature of the cold billet into the furnace is ≤80℃, and multi-stage heating is adopted, in which the total time of 500-950℃ is controlled within 0.2-0.3min / mm, the total time of 1150-1180℃ is controlled within 0.1min / mm, and the total time of 1120-1150℃ is controlled within 0.2-0.4min / mm;
[0015] Controlled rolling and controlled cooling: After the billet is taken out of the furnace, the temperature is raised to 960-1000℃ before rolling. The final rolling temperature is controlled above 910℃, the pass reduction is controlled at 20-30%, and the cooling rate after rolling is controlled at 2-5℃ / s;
[0016] 3) Off-line treatment: After the steel plate is off the line, the second stage precipitation phase and internal stress are regulated by stacking or insulation treatment, and the insulation regulation temperature is 250-400℃.
[0017] Furthermore, the steel is smelted in a converter, the Ti element in the molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.
[0018] Furthermore, the steel billet is made by converter smelting + continuous casting, and cooling begins when the surface temperature of the steel billet is 830-910°C, and the cooling rate is controlled at 3-9°C / s, followed by low-temperature heating treatment at a heating temperature of 220-370°C.
[0019] The anti-fatigue steel plate produced according to the above scheme has the following beneficial effects:
[0020] 1. The corrosion resistance of the steel plate is greatly improved by adding composite trace elements and their synergistic effect. The corrosion resistance is improved by 14-16% compared with the relative corrosion rate (64d) of 3Ni system steel of 84-86% by using the simulated South China Sea seawater splash zone immersion test.
[0021] 2. It has good comprehensive mechanical properties, structural safety and weldability, with yield strength of 420-460Mpa, yield strength ratio ≤0.75, impact energy at -40℃ not less than 180J, elongation ≥20%, and section shrinkage ≥68%.
[0022] 3. When the loading stress ratio is 0.1, the frequency is 90HZ, and the maximum stress is 0.7Rel, the number of cycles reaches 10 7 The sample does not break, -20℃CTODδm>0.62mm. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other examples improved or modified by ordinary technicians in this field belong to the scope of protection of the present invention. It should be understood that the embodiments of the present invention are only used to illustrate the technical effects of the present invention, rather than to limit the scope of protection of the present invention.
[0024] The present invention aims to solve the problem of no available materials under the complex environmental conditions of strong corrosion and large wave loads in the South China Sea. The developed steel has good mechanical properties, corrosion resistance and fatigue resistance. The corrosion resistance of the steel plate is greatly improved by adding and synergizing composite trace elements and matching preparation processes. The fatigue limit is greater than 310MPa grade fatigue-resistant steel (-20℃ CTOD≥0.6mm) is developed. It can solve the fatigue-corrosion coupling problem faced by marine structures under strong storms and large wave loads under the environmental conditions of the South China Sea in my country. It provides an effective solution for the safe service of marine structures in strong storm marine environments such as the South China Sea.
[0025] The steel composition of the present invention will be described in detail below. Unless otherwise specified, the content of each element is expressed in % by weight.
[0026] The invention discloses an anti-fatigue steel plate for use in a marine environment. The chemical composition of the steel comprises, by weight percentage, C: 0.02-0.04wt%, Si: 0.15-0.3wt%, Mn: 0.4-0.6wt%, V: 0.04-0.06wt%, N: 0.008-0.012wt%, Cu: 0.2-0.4wt%, Ni: 1-2wt%, Mo: 0.1-0.2wt%, Re: 0.021-0.034wt%, Cr: 1.5-2wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.015-0.02wt%, S: ≤0.005wt%, and the balance is Fe and unavoidable impurities.
[0027] C: 0.02-0.04wt%
[0028] C is the main phase transformation controlling element for forming the corrosion-resistant structure of the steel plate containing 55-70% bainite + 23-35% ferrite (including 6-12% acicular ferrite) as the matrix, and is an important element for ensuring the strength of the steel grade. Appropriate C promotes the important micro cathode phases V (C, N), Mo, 2 The formation of C and the precipitation of large carbides of Cr are controlled. These phases are helpful to improve the corrosion resistance of steel. Under the component system of the present invention, more C is not good for the corrosion resistance and weldability of steel, so the C content is 0.02-0.04wt%.
[0029] Si: 0.15-0.3wt%
[0030] The Si element plays a certain role in strengthening and forming surface oxides with Cr, Cu and Sn, which effectively improves the corrosion resistance. It is one of the important deoxidizers of the present invention. However, too high Si will reduce the density of the rust layer on the surface of the steel. Therefore, the Si content is controlled at 0.15-0.3wt%.
[0031] Mn: 0.4-0.6wt%
[0032] The Mn element plays a certain role in the composite control of strengthening and fatigue properties, and is one of the important deoxidizers of the present invention. Too much Mn will reduce the corrosion resistance of the steel and affect the solid solution effect of the corrosion-resistant elements in the steel. Too low Mn content is not conducive to fatigue resistance. Therefore, the Mn content is controlled at 0.4-0.6wt%.
[0033] V: 0.04-0.06wt%
[0034] The V element plays an important role in the toughness, fatigue resistance and corrosion resistance of steel mainly in the form of precipitation strengthening. The role of V in the present invention is mainly to form V (C, N) with appropriate proportions of C and N. Since the steel material is a multiphase structure formed by multi-element alloying, the control of the cathode ratio in the micro-region is very important. The refined, dispersed, uniform and distributed cathode design is very important for the control of the corrosion resistance of the complex structural system of the steel material. Based on this, the present invention adopts a trace amount of 0.04-0.06wt% of V to give full play to its excellent precipitation effect. The electrochemical impedance spectrum shows that after full precipitation, the surface inductive arc of the steel grade is greatly weakened, indicating that the pitting phenomenon is effectively suppressed. It mainly plays the role of controlling the cathode phase. Under the configuration of V, C, N and Cr elements adopted in the present invention, it will promote the generation of 10-30nm dispersed precipitation V (C, N) in the matrix of the steel, with an average spacing of 1.2-2.5μm, mainly in a spherical shape, which can further prevent the expansion of fatigue cracks. Based on the above design, the content of V is 0.04-0.06wt%.
[0035] N: 0.008-0.012wt%
[0036] The N element mainly promotes the formation of fine particles of V (C, N) and Fe 3 The complex precipitation of C and the solid solution of N help to improve the corrosion resistance of steel, but too low a content is not conducive to fatigue resistance.
[0037] Cu: 0.2-0.4wt%
[0038] Cu is an important element for corrosion resistance and mechanical properties improvement in the present invention. On the one hand, in the early stage of corrosion, after the surface is initially corroded, an enrichment layer and an oxide layer are formed, which improves the lack of significant segregation behavior. In addition, a nanophase with an average size of 17-25nm is formed inside the steel plate, and the average spacing between the phases is 1-2μm. After the surface rust layer is destroyed, a large number of fine cathode phases are further formed, which is similar to V (C, N), Mo 2 C and Fe 3 C forms a unique cathode size and distribution control system, controls the corrosion rate and helps to improve and control weldability, while too much Cu is not conducive to further exertion of corrosion resistance and fatigue performance and increases unnecessary costs. Therefore, the Cu content of the present invention is controlled at 0.2-0.4wt%.
[0039] Ni: 1-2wt%
[0040] The main function of Ni element is to balance the toughness of weathering steel. In terms of corrosion resistance, it promotes the positive movement of the self-corrosion potential on the steel surface. The present invention adopts a low Mn component design, so that Ni can more effectively promote the corrosion of Fe. 3 O 4 The formation of oxides, and Ni in the rust layer 2+Can occupy Fe more effectively 3 O 4 The interstitial position forms a stable and dense Fe and Ni intermetallic compound, preventing Cl - Diffusion into the matrix reduces acidification and increases the pH value of the electrolyte in the rust layer, so that only 1-2wt% Ni can fully achieve the corrosion resistance.
[0041] Mo: 0.1-0.2wt%
[0042] Mo element can make the rust layer dense, and when combined with Si, Cu, etc., the oxide film formed is effective against initial corrosion. In addition, along with the anodic reaction of steel, MoO 4 2- Dissolved, MoO on the rust layer 4 2- distribution, producing ion selection, resisting the corrosion promoting factor Cl - In addition, the addition of Mo helps to improve the low-temperature and high-temperature stability of the V and Cu dispersion phases, while precipitating 10-30nm Mo 2 C, improve its pitting resistance and fatigue resistance. Too high Mo will deteriorate the toughness, too low is not conducive to fatigue resistance, so it is controlled at 0.1-0.2wt%.
[0043] Re: 0.021-0.034wt%
[0044] The Re element is evenly distributed in the dendrite trunk and between dendrites during the solidification process. It is an important solid solution strengthening element. Its corrosion potential is about 0.3V, which can shift the corrosion potential positively, effectively increase the corrosion potential of the matrix, reduce the corrosion current of the system, and improve the corrosion resistance of steel. In addition, an appropriate amount of Re combined with Ni and Cu can effectively promote anode passivation and improve cathode efficiency. Since the anode current in the passivation zone is several orders of magnitude smaller than the current of activation and dissolution, it is very effective to use cathodic elements to improve the corrosion resistance of the alloy. The addition of Re helps to improve the low-temperature and high-temperature stability of the dispersed phases of V and Cu. In addition, the compound addition of Re, V, and Ni can effectively control the toughness control problem caused by the addition of elements such as Sn, so it is controlled at 0.021-0.034wt%.
[0045] Cr:1.5-2wt%
[0046] Cr; on the one hand, it plays the role of a dense rust layer, and on the other hand, it forms a passivating oxide, which together with other oxides and dense α-FeOOH resists the invasion of Cl-; in addition, in the composition design of the multi-component system of the present invention, Cr and other solid solution elements are fully dissolved in the matrix, which reduces the solid solubility of V and improves its precipitation behavior, indirectly playing a role in controlling the thermodynamic and kinetic changes of V (C, N), and after the composite effect of Cr, V and other elements forms a stable rust layer, the inductive impedance effect tends to completely disappear, indicating that the material's fatigue resistance and pitting resistance have reached the best match, and too low is not conducive to fatigue resistance. In view of environmental requirements, the Cr of the present invention is controlled at 1.5-2wt%.
[0047] REM: 0.03-0.05wt%
[0048] On the one hand, REM rare earth elements can change the size of cathode phases such as V (C, N), increase their dispersion, increase their potential, and reduce their cathode effect. Because the content reaches 0.03-0.05wt%, it is fully dissolved in the matrix, which plays a role in increasing the matrix potential and directly produces corrosion resistance. The RE absorbed by grain boundaries, subgrain boundaries, precipitate mismatches and other positions plays a role in balancing the segregation of elements such as Cr and Cu, reducing intergranular and interphase corrosion caused by segregation.
[0049] Sn: 0.05-0.1wt%
[0050] On the one hand, Sn element can reduce the energy level of steel and weaken the electrochemical activity of steel in the form of single substance solid solution. In addition, it helps to form oxides such as SnO and deposit on the corrosion front, promote the formation of α-FeOOH, and compact the oxide layer together with α-FeOOH. When dissolved with Fe, ionic Sn can react with Cl - In combination, the local pH value is increased to control the acceleration of the corrosion process. According to environmental requirements, the Sn content of the present invention is controlled at 0.05-0.1wt%.
[0051] Ti: 0.001-0.005wt%
[0052] The Ti element helps to control the initial grain size, but too much will consume the N element, affecting the strength and corrosion resistance of the steel. Therefore, the Ti content of the present invention is controlled within 0.001-0.005 wt%.
[0053] P: 0.015-0.02wt%
[0054] The P element is mainly used to reduce the degree of anode polarization, promote the uniform dissolution of steel and accelerate the oxidation rate of iron, promote the formation of non-static protective film, and cooperate with Re, Cu, etc. to resist Cl -However, too much P reduces the weldability of the steel. Taking the converter smelting process as an example, no special control is required. Therefore, the P of the present invention is controlled at 0.015-0.02wt%.
[0055] S:≤0.005wt%
[0056] S: The sulfide formed by the element accelerates corrosion and reduces the toughness of the steel plate, so it needs to be strictly controlled to ≤ 0.005wt%.
[0057] In addition to the above-mentioned steel components, the balance of the present invention may be Fe and inevitable impurities. Inevitable impurities are impurities that are not artificially mixed in the general steel manufacturing process. They cannot be completely excluded, and the meaning can be easily understood by those skilled in the art of general steel manufacturing. In addition, the present invention does not completely exclude the addition of other components in addition to the above-mentioned steel components.
[0058] The microstructure of the present invention will be described in further detail below.
[0059] The invention discloses an anti-fatigue steel plate in marine environment, wherein the average grain size of the surface layer -1 / 8 of the thickness of the steel plate is 15-25 μm, the steel plate contains a corrosion-resistant structure of 55-70% bainite + 23-35% ferrite (including 6-12% acicular ferrite), and the percentage is the area percentage; and contains dispersed precipitated V (C, N) and Mo 2 C nanophases, the size of these phases is 10-30nm, the average size is 15-25nm, the average spacing is 1.2-2.5μm, and they contain dispersed Cu nanophases, the size of these phases is 15-30nm, the average size is 17-25nm, and the average spacing between the phases is 1-2μm.
[0060] The production process of the present invention is described in further detail below.
[0061] A method for producing fatigue-resistant steel plates in marine environments, including smelting, continuous casting, billet heating, controlled rolling and controlled cooling, and off-line processing, the specific contents of which are as follows:
[0062] Smelting: The steel is smelted in a converter + refined + vacuum degassing. Si and Mn are used for deoxidation, and the use of Al is strictly controlled because the addition of Al will consume the N element and have a harmful effect on the surface quality of the steel billet. Similarly, the introduction of Ti elements in the molten iron used must also be strictly controlled (controlled below 0.005%) to affect the precipitation effect of V and Cu and avoid the formation of Ti, Al, Nb and other carbonitrides, which are not good for corrosion resistance.
[0063] Continuous casting: The steel billet is made by converter smelting + continuous casting. In order to control the initial surface grain size of the continuous casting billet and the solid distribution of elements such as Re, W, Mo, Cu, Ni, Cr, etc., it plays the role of a dense rust layer. When the billet is discharged, the rapid cooling method is used for pretreatment. The surface temperature of the cold start is controlled at 830-910℃, and the cooling rate is controlled at 3-9℃ / s. After that, it is not suitable for hot loading. Low-temperature heating treatment is required, and the treatment temperature is 220-370℃ to control the surface quality and thermal stress distribution of the steel billet.
[0064] Billet heating: The temperature of the cold billet in the furnace is controlled at ≤80℃, and multi-stage heating is adopted, in which the total time of 500-950℃ is controlled within 0.2-0.3min / mm, the total time of 1150-1180℃ is controlled within 0.1min / mm, and the total time of 1120-1150℃ is controlled within 0.2-0.4min / mm. The purpose is to control the initial distribution of alloy elements and trace elements before hot working. Since the distribution and composition of grains, especially grain boundaries, have a greater impact on corrosion, it is necessary to reasonably control the initial grain size.
[0065] Controlled rolling and controlled cooling: high temperature controlled high pressure rolling is adopted. Specifically, the billet is rolled after being heated to 960-1000℃ after being taken out of the furnace. The final rolling temperature is controlled at above 910℃. The reduction of each pass in this stage is controlled at 20-30%. After rolling, the austenite phase transformation zone is quickly passed by rapid cooling. The cooling rate is controlled at 2-5℃ / s. The purpose is to balance the phase transformation and grain size. The surface grain size is controlled, and the average grain size of the surface layer of the steel plate -1 / 8 thickness is controlled at 15-25μm. The distribution state of the surface corrosion-resistant elements is controlled, the precipitation of elements such as V, Cu, and Mo is suppressed, and the components in the steel are supercooled. In addition, the control of the surface grain size can ensure the balance of mechanical and corrosion resistance. The above process forms a corrosion-resistant structure with 55-70% bainite + 23-35% ferrite (including 6-12% acicular ferrite) as the matrix.
[0066] Off-line treatment: After the steel plate is off the line, the second stage precipitation phase and internal stress are regulated by stacking and heat preservation treatment. The heat preservation temperature is 250-400℃. On the one hand, the surface hardness can be regulated to improve the mechanical properties of the steel plate surface. On the other hand, finer precipitations are formed to improve the overall corrosion resistance of the steel plate. After the regulation, V(CN), VN and Mo with a size of 10-30nm (average size 15-25nm) are dispersed in the steel matrix. 2 C, the average spacing between these phases is 1.2-2.5μm, and there are also 15-30nm (average size 17-25nm) Cu nanophases in the matrix, and the average spacing between the phases is 1-2μm.
[0067] According to the above chemical composition and production process, the actual smelting composition of the present invention is shown in Table 1, the actual process parameters of the present invention are shown in Tables 2-4, and the actual properties are shown in Tables 5-8.
[0068] Table 1 Composition of each embodiment
[0069] C To <![CDATA[M n ]]> V N <![CDATA[C u ]]> In Know <![CDATA[R e ]]> <![CDATA[C r ]]> SOAK <![CDATA[S n ]]> P S Of 1 0.02 0.3 0.57 0.041 0.01 0.25 1.58 0.18 0.025 2 0.04 0.09 0.016 0.002 0.03 2 0.02 0.17 0.56 0.04 0.009 0.4 1.02 0.09 0.024 1.81 0.03 0.07 0.019 0.002 0.02 3 0.03 0.19 0.43 0.043 0.011 0.21 1.77 0.18 0.034 1.76 0.035 0.09 0.018 0.002 0.02 4 0.02 0.27 0.46 0.041 0.008 0.39 1.24 0.17 0.032 2 0.03 0.08 0.016 0.001 0.03 5 0.03 0.16 0.6 0.05 0.009 0.33 1.36 0.2 0.021 1.96 0.04 0.05 0.015 0.003 0.01 6 0.03 0.22 0.41 0.059 0.007 0.3 1.92 0.15 0.031 1.59 0.043 0.09 0.019 0.001 0.03 7 0.03 0.18 0.46 0.046 0.009 0.29 1.62 0.15 0.022 1.93 0.04 0.07 0.02 0.002 0.03 8 0.02 0.17 0.55 0.045 0.008 0.32 1.45 0.14 0.034 1.85 0.042 0.06 0.016 0.003 0.01 9 0.02 0.29 0.42 0.052 0.012 0.25 2 0.16 0.026 1.5 0.05 0.08 0.019 0.002 0.03 10 0.03 0.2 0.42 0.05 0.008 0.37 1.84 0.19 0.027 1.82 0.037 0.09 0.015 0.002 0.03
[0070] Table 2 Steel pretreatment
[0071]
[0072]
[0073] Table 3 Heating process
[0074]
[0075] Table 4 Rolling process and offline process
[0076]
[0077] Table 5 Steel plate microstructure ratio
[0078]
[0079] Table 6 Tensile and impact properties of the examples
[0080]
[0081] Table 7 Fatigue properties of the examples
[0082]
[0083] Table 8 Corrosion resistance of the examples (g / m 2 .h)
[0084]
[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A fatigue-resistant steel plate for marine environment, characterized in that: The chemical composition of the steel grade includes C: 0.02-0.04wt%, Si: 0.15-0.3wt%, Mn: 0.4-0.6wt%, V: 0.04-0.06wt%, N: 0.008-0.012wt%, Cu: 0.2-0.4wt%, Ni: 1-2wt%, Mo: 0.1-0.2wt%, Re: 0.021-0.034wt%, Cr: 1.5-2wt%, REM: 0.03-0.05wt%, Sn: 0.05-0.1wt%, Ti: 0.001-0.005wt%, P: 0.015-0.02wt%, S: ≤0.005wt %, the balance is Fe and unavoidable impurities; the steel plate contains 55-70% bainite + 23-35% ferrite structure, the percentages are area percentages; it contains V (C, N) and Mo2C nanophases with an average size of 15-25nm dispersed and precipitated, the average spacing of these phases is 1.2-2.5μm, and contains Cu nanophases with an average size of 17-25nm, the average spacing of Cu nanophases is 1-2μm; 23-35% ferrite contains 6-12% acicular ferrite; the size of the dispersed precipitated V (C, N) and Mo2C nanophases is 10-30nm, and the size of the Cu nanophase is 15-30nm; the average grain size of the surface layer -1 / 8 of the thickness of the steel plate is 15-25μm.
2. The fatigue-resistant steel plate for marine environment according to claim 1, characterized in that: The yield strength of the steel is 420~460MPa, the yield strength ratio is ≤0.75, the impact energy at -40℃ is not less than 180J, the elongation is ≥20%, and the section shrinkage is ≥68%.
3. The fatigue-resistant steel plate for marine environment according to claim 1, characterized in that: When the loading stress ratio is 0.1, the frequency is 90HZ, and the maximum stress is 0.7Rel, the number of cycles reaches 10 7 The sample does not break, -20℃ CTOD>0.62mm.
4. The fatigue-resistant steel plate for marine environment according to claim 1, characterized in that: Using a simulated South China Sea seawater splash zone immersion test, the corrosion resistance was 84-86% relative to 3Ni system steel.
5. A method for producing fatigue-resistant steel plates for marine environments according to any one of claims 1 to 4, characterized in that: It includes smelting, continuous casting, billet heating, controlled rolling and cooling, and off-line processing. The specific contents are as follows: Billet heating: The temperature of the cold billet into the furnace is ≤80℃, and multi-stage heating is adopted, in which the total time of 500-950℃ is controlled within 0.2-0.3min / mm, the total time of 1150-1180℃ is controlled within 0.1min / mm, and the total time of 1120-1150℃ is controlled within 0.2-0.4min / mm; Controlled rolling and controlled cooling: After the billet is taken out of the furnace, the temperature is raised to 960-1000℃ before rolling. The final rolling temperature is controlled above 910℃, the pass reduction is controlled at 20-30%, and the cooling rate after rolling is controlled at 2-5℃ / s; Off-line treatment: After the steel plate is off the line, the second stage precipitation phase and internal stress are regulated by stacking or insulation treatment, and the insulation control temperature is 250-400℃.
6. The method for producing fatigue-resistant steel plates in marine environments according to claim 5, characterized in that: The steel is smelted in a converter, the Ti element in the molten iron is controlled below 0.005%, and Si and Mn are used for deoxidation.
7. The method for producing fatigue-resistant steel plates in marine environments according to claim 5, characterized in that: The steel billet is made by converter smelting + continuous casting. The steel billet starts to cool when the surface temperature is 830-910°C, and the cooling rate is controlled at 3-9°C / s. It is then subjected to low-temperature heating treatment at a heating temperature of 220-370°C.
Citation Information
Patent Citations
High-anticorrosion low alloy steel suitable for high-temperature littoral environment
CN106929751A
High-performance steel plate resistant to corrosion of marine total immersion zone and production method of high-performance steel plate
CN113549818A
Marine seawater corrosion fatigue resistant ultrahigh strength steel and manufacturing method thereof
CN114836694A